Insania quae medicis traditur : A testi eredetű pszichés zavarok jelensége Seneca filozófiai és Aretaios orvostudományi szövegének tükrében - Bán, Katalin (Antikvitás & Reneszánsz, 2019)
In my study, I intend to examine and compare Seneca’s and Aretaeus’s views about madness of physical origins, as we can observe several connection points of this mental state in their medical and philosophical treatises. Seneca distinguishes between two types of insania, and as a philosopher, puts more emphasis on the “usual madness” of those who are in the grip of passions, but also deals with the madness of those who are medically ill and treated by medical doctors (insania publica et quae medicis traditur). Aretaeus as a physician approaches the phenomenon mainly from a medical point of view, but beyond biological causes, also pays attention to the manifestation of mental disorders due to emotions, that is, he expresses that purely passions and emotions are able to cause mental disorder. We can observe that both of them expresses a specific blend of these two types of insania, which shows how much contemporary philosophy and medicine were intertwined in spite of their separation.